Gonadotrofina coriónica humana y su relación con la función luteal y la respuesta reproductiva en ovinos - Catalano, R. (2016)
This paper describes the different physiological processes of luteal function in relation to the maintenance of pregnancy. A review of the results evaluating the effects of the application of human chorionic gonadotropin (hCG) in order to reduce embryonic losses is presented. From this analysis it is suggested that hCG could be applied in sheep in order to stimulate the synthesis of luteal progesterone, the formation of accessory corpora lutea, uterine and placental function, fetal growth, fertility and prolificacy.